German efforts to develop agriculture in Cameroon in the first quarter of the twentieth century (Journal of the College of Basic Education, 2023)
This research discussed the interest shown by the German colonialism in Cameroon in natural resourcesAgricultural, animal and mineral. The ways of this interest were discussed in detail through a detailed explanation of the matterAgricultural programs and those related to livestock, which led to improving this wealth and increasing its productivity as a wholeAnd kind. The research also discussed the types and varieties of plants and crops, and what they produce in accurate, well-marked numbersFrom German official records. The research did not exceed the role of scientific research in saving large numbers ofLivestock that was perishing due to epidemics that afflict them, increasing their numbers and improving their quality. alsoThe research discussed the interest of German colonialism in mineral wealth and the mining industry, as it extracted manyMetals with commercial quantities that are used in various industries.